PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING PADA UMKM D’CIWIL CIRENG KRIWIL VAVA HOUSE DI PALEMBANG - Sutandi, Sri (Institut Rahmaniyah Sekayu, 2024)
Production price is all costs related to a product which some of them are elements of production cost such as raw materials, direct labour, and overhead manufactory. This cost production is used by the business owner to determine the selling price which will be sold to consumers. Production price will determine the earned income level, if the price production determination is incorrect, the income determination will also be incorrect. There are some methods used in determining the production price, those are full costing method and variable costing method. The location of this research was at D’Ciwil Cireng Kriwil Vava House, Jalan Sentosa Lorong Sriraya 6 No. 39 Rt. 42 Rw. 15, Kelurahan Plaju Ulu, Kecamatan Plaju Kota Palembang, South Sumatera. This research was carried out by comparing full method costing and varible costing method. Full costing method was the most appropriate method for D’Ciwil Cireng Kriwil Vava House micro, small and medium enterprise, because it included all elements of cost incurred and had been divided, so that the calculation of price production would be more appropriate and accurate and also could increase the profit of D’Ciwil Cireng Kriwil Vava House micro, small and medium enterprise with the determination of the right selling price.